2017
DOI: 10.1038/ja.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial sulfonamides clear latent Kaposi sarcoma herpesvirus infection and impair MDM2–p53 complex formation

Abstract: Kaposi Sarcoma Herpesvirus (KSHV), also known as Human Herpesvirus 8, is the causative agent of Kaposi sarcoma; this malignant angiosarcoma is usually treated with conventional anti-tumor agents, which can control disease evolution, but do not clear the latent KSHV episome that binds to cellular DNA. Some commercial antibacterial sulfonamides were tested for the ability to suppress latent KSHV. qPCR and cytofluorometry assays were used for detecting both viral DNA and the latency factor LANA in BC3 cells, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The results showed that the sulfadoxine-pyrimethamine combination combined with antiretroviral therapy significantly enhanced HIV replication in MT-2 cells, while it inhibited HIV replication in peripheral blood mononuclear cells [23]. Moreover, recent studies have demonstrated that sulfonamides can act on latent herpesviruses, such as EBV and Kaposi sarcoma herpesvirus (KSHV) [182,183]. Furthermore, a work conducted by Angius and colleagues reported that sulfonamide antibiotics suppressed the KSHV latent state in permanently infected lymphoma cells [183].…”
Section: Sulfonamidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the sulfadoxine-pyrimethamine combination combined with antiretroviral therapy significantly enhanced HIV replication in MT-2 cells, while it inhibited HIV replication in peripheral blood mononuclear cells [23]. Moreover, recent studies have demonstrated that sulfonamides can act on latent herpesviruses, such as EBV and Kaposi sarcoma herpesvirus (KSHV) [182,183]. Furthermore, a work conducted by Angius and colleagues reported that sulfonamide antibiotics suppressed the KSHV latent state in permanently infected lymphoma cells [183].…”
Section: Sulfonamidesmentioning
confidence: 99%
“…Moreover, recent studies have demonstrated that sulfonamides can act on latent herpesviruses, such as EBV and Kaposi sarcoma herpesvirus (KSHV) [182,183]. Furthermore, a work conducted by Angius and colleagues reported that sulfonamide antibiotics suppressed the KSHV latent state in permanently infected lymphoma cells [183]. This result suggested that sulfonamides might play a potential role in clearing KSHV-infected lymphoma cells.…”
Section: Sulfonamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Paul et al [22] demonstrated that a known sulfone drug, namely nimesulide, can affect HHV8 latency by interacting with its binding to cell DNA. In addition, some sulfonamide drugs have recently been shown to be able to interfere with the binding of LANA to the cellular DNA [23]. It is worth noting that several other DNA (e.g., Adenoviruses and Herpesviruses) and RNA (e.g., Rubella, Dengue virus, Enteroviruses, Hepatitis C virus and HIV) viruses were found to be able to affect the host's metabolism favouring not only the onset of tumours but also some other chronic diseases, namely metabolic syndrome and diabetes [4,[24][25][26][27][28][29].…”
Section: Virology and Molecular Biology Of Hhv8mentioning
confidence: 99%
“…Whether GHVs inhibit p53 as a matter of course during latency has become controversial.Although KSHV LANA was demonstrated to potently inhibit p53(26), several subsequent studies have challenged this original finding. PEL cells harboring latent KSHV and expressing high levels of LANA, as well as other latency-associated transcripts, remain sensitive to p53 agonists, responding to treatment with potent p53 stabilization, p53-related gene expression, and cell death(28,71,72). In contrast, KSHV-infected cells are resistant to p53-mediated death during lytic replication(73).…”
mentioning
confidence: 99%